The Effects of Measurement Concepts on The Investment Decisions of Trustees. - Williamson, James E. (The Accounting Review, 1971)
A normative model of expected behavior was developed and used to evaluate the effects of measurement concepts on the investment policy decisions of trustees. Traditional concepts of trust income and trust corpus were compared with purchasing power concepts. It was found that traditional concepts affect investment policy decisions in three ways. (1) Defining income as cash dividends and interest could create constraints that would not allow the selection of a portfolio for the trust on the basis of risk-yield preference. (2) Constraints imposed by attempts to offset the effects of secular inflation could cause the selection of portfolios not considered optimal on the basis of risk-yield preference. (3) The differential tax features of securities can cause the selection of a sub-optimal port- folio in order to avoid appearing biased. Investment policy decisions under the purchasing power concepts do not appear to be affected by the first two constraints, but could be affected by constraints imposed by the differential tax treatment of securities; this would depend upon whether the distribution formulation considered tax effects. Many (if not most) state statutes would preclude this approach to the problem. Although this does not mean the statutes are preferable, the purchasing power concepts, though theoretically sound, are probably not capable of implementation under current conditions. It is possible, however, through direct specifications in the terms of the trust, to achieve many of the advantages that would be gained by utilizing purchasing power concepts. The primary advantage would be to free the trustee's investment decisions from constraints caused by the conflict of interests between life tenants and remaindermen.